Management of an extensive frontal pyocoele using an external approach: a case report - Hussain, Syed Ahmed Shahzaeem; Hussain, Syed Ahmed Shahzain; Hussain, Syed Muzahir (Journal of the Pakistan Medical Association, 2022)
Pyocoeles of the paranasal sinuses are pus-filled cavities seen in the sinuses and develop from the infection of the mucocoeles. Pyocoeles most commonly form in the frontal sinus. Endoscopic Sinus Surgery is currently the mainstay of the treatment. We present the case of an 85-year-old female who presented to the ENT OPD of Jinnah Hospital/AIMC, Lahore, in October 2017 with complaints of progressive symptoms of intractable left frontal pain, double vision, and an associated swelling below the medial half of the left eyebrow. A CT scan was done and a diagnosis of extensive frontal pyocele was made. She was treated successfully with an external approach and remained without any complications till 13-month follow-up after surgery; exceptional cosmetic results were achieved. We wish to bring attention to the possibility of an external approach being used as a primary intervention, if deemed appropriate.